1996
DOI: 10.1289/ehp.961041141
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of environmental benzene exposure.

Abstract: Environmental exposures to benzene result in increases in body burden that are reflected in various biomarkers of exposure, including benzene in exhaled breath, benzene in blood and urinary trans-trans-muconic acid and S-phenylmercapturic acid. A review of the literature indicates that these biomarkers can be used to distinguish populations with different levels of exposure (such as smokers from nonsmokers and occupationally exposed from environmentally exposed populations) and to determine differences in meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The reported values for PMA corresponding to 1 ppm benzene cluster around 40 µg/g cr with two extremes of 12 and 58 µg/g cr. In making comparison with the present observation (Table 4), it should be noted that the benzene exposure in the present study (up to 210 ppm) is much higher than the levels reported for the populations in literature (up to 20 ppm), and that possibility exists that the metabolism of benzene may vary depending on the exposure intensity 34) . Nevertheless, it appears likely that there is a general agreement between the present observation and findings available in literature, when urinary PMA level corresponding to 1 ppm benzene exposure is estimated from individual regression equations (the rightmost column in Table 4).…”
Section: Discussionsupporting
confidence: 65%
“…The reported values for PMA corresponding to 1 ppm benzene cluster around 40 µg/g cr with two extremes of 12 and 58 µg/g cr. In making comparison with the present observation (Table 4), it should be noted that the benzene exposure in the present study (up to 210 ppm) is much higher than the levels reported for the populations in literature (up to 20 ppm), and that possibility exists that the metabolism of benzene may vary depending on the exposure intensity 34) . Nevertheless, it appears likely that there is a general agreement between the present observation and findings available in literature, when urinary PMA level corresponding to 1 ppm benzene exposure is estimated from individual regression equations (the rightmost column in Table 4).…”
Section: Discussionsupporting
confidence: 65%
“…Recently, in a number of countries, the occupational exposure limit for airborne benzene has been lowered to 1 ppm (8-hour time-weighted average). Weisel et a1 (7) reported that automobile mechanics were exposed to a mean concentration of 1 ppm, and workers at a chemical plant had benzene exposure with a geometric mean level of 0.1 ppm for both smokers and nonsmokers. Therefore, it is very meaningful to verify the suitability of S-PMA and t,t-MA as exposure biomarkers which allow the detection of low concentrations of benzene and to apply their biomonitoring for the monitoring of occupational exposure and environmental pollution from benzene in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…However, biomarker data are often difficult to obtain, and the relationship between biomarkers of exposure and dose is usually not straightforward (Weisel et al, 1996;Roy and Georgopoulos, 1998), as is evident by considering the factors that affect the blood concentrations of benzene and lead. Exposure to benzene generally occurs via inhalation, which has an immediate impact on blood concentrations, whereas lead exposure generally occurs via ingestion, which has a delayed effect on blood concentration, as the ingested lead is absorbed into systemic circulation over a period of time.…”
Section: Discussionmentioning
confidence: 99%